2013
DOI: 10.3839/jabc.2013.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cheonggukjang Made from Sword Bean on Serum Lipid Profile and Tissue Change in Rats

Abstract: This study was to investigate serum triglyceride (TG), phospholipid (PL), and cholesterol concentrations after feeding the combined diets of prepared traditional Cheonggukjang (TC) or Cheonggukjang made from sword bean powder (CS), the feed, and high-fat cholesterols at certain ratio for 8 weeks in rats, and then confirmed the effects of the diets based on the changes in the tissues of livers, kidneys, and spleens. The serum TG concentrations were lower in CS group compared to that of in TC group. The increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Immunity is the host's defense system present in animals that protects against disease or other foreign bodies. In the host, both innate and adaptive immune system has evolved to respond to eradicate pathogens 49 . The in vitro and in vivo studies of sword bean have been reported to be anti-allergic and anti-inflammatory effect 50 .…”
Section: Anti-inflammatory and Immunological Activitesmentioning
confidence: 99%
“…Immunity is the host's defense system present in animals that protects against disease or other foreign bodies. In the host, both innate and adaptive immune system has evolved to respond to eradicate pathogens 49 . The in vitro and in vivo studies of sword bean have been reported to be anti-allergic and anti-inflammatory effect 50 .…”
Section: Anti-inflammatory and Immunological Activitesmentioning
confidence: 99%
“…Sword bean, scientifically known as Canavalia gladiata Jacq., is a tropical and sub-tropical legume plant that is primarily grown for its edible beans and attractive flowers. The most notable feature of the sword bean plant is its long, flat and somewhat sword-shaped pods [2]. These pods measure about 20 to 40 cm (7.87 to 15.75 inches) in length and are typically green, turning yellow or brown as they mature.…”
Section: Introductionmentioning
confidence: 99%